Amplification Techniques for the Detection of Misfolded Prion Proteins in Experimental and Clinical Samples. Issue 1 (9th March 2020) - Haley, Nicholas
Abstract: This article describes two methods for amplifying prions present in experimental and clinical samples: the protein misfolding cyclic amplification (PMCA) assay and the real‐time quaking‐induced conversion (RT‐QuIC) assay. Protocols for preparation of amplification substrate and analysis of results are included in addition to those for the individual assays. For each assay, control and suspect samples are mixed with appropriate amplification substrate, which is whole brains from mice in the case of PMCA and recombinant prion protein produced in bacteria for RT‐QuIC, followed by cyclic amplification over a number of cycles of sonication (PMCA) or shaking (RT‐QuIC) at a consistent incubation temperature. The resultant amplification products are then assessed either by western blotting (PMCA) or based on fluorescent emissions (RT‐QuIC). The equipment and expertise necessary for successfully performing either assay vary and will be important factors for individual laboratories to consider when identifying which assay is more appropriate for their experimental design. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Prion amplification via protein misfolding cyclic amplification Support Protocol 1 : Collection of whole brains from mice and preparation of normal brain homogenate Basic Protocol 2 : Prion amplification via real‐time quaking‐induced conversion Support Protocol 2 : Preparation of recombinant truncated white‐tailed‐deer prion protein